1998
DOI: 10.1111/j.1439-0329.1998.tb01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of oak stand decline with special reference to the role of drought in Poland

Abstract: Declines in oak-forest ecosystems have been reported frequently throughout the world since the beginning of this century. They have been assoeiated with the death of individual trees, of small groups of trees or of entire stands. In this paper, the phenomenon of oak decline is presented in the context of the local site eonditions in seleeted eountries. Oak deeline is regarded as a result of the synergistic aetion between damaging agents, both biotie and abiotie. Periodic changes of the climate in selected expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 6 publications
2
41
0
Order By: Relevance
“…3). This is in agreement with the results of other European studies, which have shown a clear negative effect of summer water deficit on oak growth (Osipov, 1989;Tessier et al, 1994;Bridge et al, 1996;Siwecki and Ufnalski, 1998;Kelly et al, 2002). In addition, while higher summer temperatures had a negative impact on growth, it was not as pronounced as was the positive impact of precipitation (Fig.…”
Section: Growth and Monthly Weather Conditionssupporting
confidence: 82%
See 1 more Smart Citation
“…3). This is in agreement with the results of other European studies, which have shown a clear negative effect of summer water deficit on oak growth (Osipov, 1989;Tessier et al, 1994;Bridge et al, 1996;Siwecki and Ufnalski, 1998;Kelly et al, 2002). In addition, while higher summer temperatures had a negative impact on growth, it was not as pronounced as was the positive impact of precipitation (Fig.…”
Section: Growth and Monthly Weather Conditionssupporting
confidence: 82%
“…The clear negative association between growth and water deficit, however, points to reduced hydraulic conductance of shoots, and, as a result, limits stomatal conductance and carbon assimilation during drought periods (Rust and Roloff, 2002). Previous studies indicated that oak sensitivity to water stress is especially high during spring and early summer (Bridge and Winchester, 2000;Siwecki and Ufnalski, 1998).…”
Section: Growth and Monthly Weather Conditionsmentioning
confidence: 99%
“…in the Chojnów Forest District (Masovian Voivodship) and Krotoszyn Forest District (Wielkopolskie Voivodship, Table 1), where the process of oak decline has been observed for several years (Siwecki and Ufnalski 1998). The forest within each study site was dominated by Q. robur.…”
Section: Methodsmentioning
confidence: 99%
“…The implication of drought in oak stand decline was demonstrated in France (after the 1976' drought [13], after the 1989-1991 dry sequence [20]), in Poland [130], and in all Central Europe wide [142]. Nevertheless, the latter authors proposed a conceptual model of the interaction of abiotic (drought) and biotic factors (defoliation for two consecutive years) responsible for the onset of oak decline.…”
Section: Drought Induced Mortalitymentioning
confidence: 99%